Academic Supervision by Madrasah Principals in Improving Teachers Pedagogical Competence and Developing Students Potential - Firdaus, Firdaus; Prasetiyo, Teguh; Majid, Abdul; Shiddiq, Ngarifin; Fatkhana, Nafila Nuru (Journal of Education Technology and Inovation, 2025)
This study investigates the implementation of academic supervision by madrasah principals to improve teachers' pedagogical competence and to support the development of students' potential. Teachers are expected to demonstrate strong pedagogical competence, and principals play a strategic role in guiding and assisting teachers through effective academic supervision. This research aims to examine how academic supervision is conducted and how it enhances teachers' competence and student development. A qualitative multi-case study approach was employed, involving observations, interviews, and document analysis in two madrasahs. The findings indicate that academic supervision is implemented through direct feedback, in-service training, recommendations for professional development programs, and the preparation of supervision reports to monitor teacher progress. However, the follow-up stage of supervision has not been optimally executed due to the lack of systematic reporting from training activities and professional discussions attended by teachers. In conclusion, although academic supervision has been carried out in a structured manner, its impact on improving pedagogical competence and developing students' potential is not yet maximal, highlighting the need for stronger follow-up mechanisms and continuous evaluation.